1999
DOI: 10.1021/la9900876
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block Copolymers as Efficiency Boosters for Microemulsions

Abstract: We demonstrate that block copolymers of the poly(ethylenepropylene)-co-poly(ethylene oxide) (PEP−PEO) type dramatically enhance the solubilization capacity of medium-chain surfactants in microemulsions, for example, in the ternary system water−n-decane−C10E4. The effect exhibits itself in an enormous increase of the swelling of the middle phase with an associated increase in the structural length scale of the microemulsion, while at the same time the (already ultralow) interfacial tension between water- and oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 28 publications
8
147
0
Order By: Relevance
“…Therefore, it was suggested that EPDME(14/7) enhanced the solubilizing ability of PO7/EO30-PS for BEMT. A previous study has reported a similar result; the solubilization quantity of oil increased when a polyoxyethylene/polyoxypropylene block co-polymer was used as a booster 19,20) . Moreover, even a phytosterol surfactant having lowest hydrophilicity, such as PO20/EO20-PS, showed a higher solubilizing ability than EO30-PS, when BEMT was solubilized by the preparation method with EPDME(14/7) ( ).…”
Section: 17supporting
confidence: 64%
“…Therefore, it was suggested that EPDME(14/7) enhanced the solubilizing ability of PO7/EO30-PS for BEMT. A previous study has reported a similar result; the solubilization quantity of oil increased when a polyoxyethylene/polyoxypropylene block co-polymer was used as a booster 19,20) . Moreover, even a phytosterol surfactant having lowest hydrophilicity, such as PO20/EO20-PS, showed a higher solubilizing ability than EO30-PS, when BEMT was solubilized by the preparation method with EPDME(14/7) ( ).…”
Section: 17supporting
confidence: 64%
“…In addition, nonionic surfactants have a great capacity of hydration by their ethoxylated (EO) units; hence, an appropriate selection of surfactant, oil and precursor salts/precipitating agent concentration, in combination with the rich structural behavior that such a system may display as a function of temperature, can lead to highly optimized formulations in terms of aqueous phase uptake and hence reactants loading. A good premise to this behavior is the enormous efficiency boost in the formation of middle phase microemulsions by the use of block copolymer surfactants reported by Strey et al (Jakobs et al, 1999).…”
Section: Microemulsions and Phase Equilibriamentioning
confidence: 98%
“…glyceryl tri(2-ethylhexanoate) and di(2-ethylhexyl) succinate) and water. On the other hand, because EPDME is a random copolymer and differs from a block copolymer that cam make micelle structure in water [12][13][14][15][16] , EPDME is unable to form self-assemble structure by itself.…”
Section: Introductionmentioning
confidence: 99%